Long-term outcomes of surgical management in subtypes of Chiari malformation. (2nd September 2021) - Basaran, Recep; Bozdogan, Caglar; Senol, Mehmet; Gundogan, Dogan; Isik, Nejat
ABSTRACT: Objective : Chiari malformations (CMs) are a heterogeneous group of disorders defined by anatomic anomalies of the cerebellum, brainstem, and craniovertebral junction (CVJ). The aims of this study are to establish the demographic and clinical features, incidence, surgical procedures, and outcomes in large series of old and new subtypes of CMs. Material and Methods : All patients were evaluated and operated on for CM-0, 1, and 1.5 between 1985 and 2016. The patients were grouped into various subtypes. Demographic data, additional diseases, clinical features, surgical procedures, complications and outcomes were recorded. Results : 191 patients who underwent various surgical procedures were evaluated. Their mean age was 37.21 ± 9.89. We detected 15 cases of CM-0 (7.8%), 121 cases of CM-1 (63.4%), 55 cases of CM-1.5 (28.8%). In total there were 191 cases, and 220 surgical procedures were performed. 29 (13.2%) of all surgical procedure was reoperations and secondary operations. SM Cyst is found to be decreased in 72 (76.5%) patients, unchanged in 14 (14.8%) and increased in 8(8.5%) of 94 patients radiologically. Clinical outcomes are better for 131 (65.8%), same for 31 (16.2%) and worse for 9 (15%). Conclusion : This study with 172 patients is a large series that includes CM-0, 1, and 1.5 subtypes. CM-1.5 also differs for symptom presentation and durations from CM-1. There are more neurological abnormalities in patients with SM. CVD alone are an effective, useful and safe surgical procedure for CM-0, CM-1 and CM-1.5. Surgical procedure, SM existence, and symptom duration have powerful effects on outcomes.